An Information Security Strategy for Networkable Devices. - Oshri, I. (IEEE Security and privacy : building confidence in a networked world)
Networkable Windows-based operating system devices present information security challenges to both vendors and users of such devices. This article highlights some of those threats and offers measures to improve the link between a firm's business strategy, its operational activities, and its information security strategy.